Using nuclear observations to improve climate research and GHG emission estimates – the NuClim project - Barbosa Susana; Chambers Scott; Pawlak Wlodzimierz; Fortuniak Krzysztof; Paatero Jussi; Röttger Annette; Röttger Stefan; Chen Xuemeng; Melintescu Anca; Martin Damien; Kikaj Dafina; Wenger Angelina; et al. (EPJ Nuclear Sciences & Technologies)
Project NuClim (Nuclear observations to improve Climate research and GHG emission estimates) aims to use high-quality measurements of atmospheric radon activity concentration and ambient radioactivity to advance climate science and improve radiation protection and nuclear surveillance capabilities. It is supported by new metrological capabilities developed in the EMPIR project 19ENV01 traceRadon. This work reviews the scientific objectives of project NuClim in terms of both climate science and radiological protection, and provides an overview of the NuClim field campaign and the various nuclear measurements being implemented within the scope of the project.